Effect of ethylene vinyl acetate (EVA) closed cell foam on transmitted forces in mouthguard material. Issue 3 (1st June 2002) - Westerman, B; Stringfellow, P M; Eccleston, J A; Harbrow, D J
Abstract : Objectives: To compare transmitted forces through ethylene vinyl acetate (EVA) mouthguard material and the same EVA material with gas inclusions in the form of a closed cell foam. Method: EVA mouthguard materials with and without foam gas inclusions and 4 mm thick were impacted with a constant force from an impact pendulum. Various porosity levels in the foam materials were produced by 1%, 5%, and 10% by weight foaming agent. The forces transmitted through the EVA after energy absorption by the test materials were measured with a force sensor and compared. Results: Only minor non-significant differences in transmitted forces through the EVA with and without foam were shown. Conclusions: The inclusion of gas in the form of a closed cell foam in 4 mm thick EVA mouthguard materials did not improve the impact performance of the EVA mouthguard material.